Ultrastructural studies of fresh, frozen-thawed and acrosome-reacted goat sperm - Abdullah, Ramli; Mat Noor, M.; Hashida, N.H.; Rajikin, M.H. (2005)
Data on the ultrastructure of sperm subjected to freezing and acrosome reaction treatment are lacking. The present study was undertaken to investigate the effects of sperm freezing and acrosome reaction on the ultrastructure of the goat sperm. The sperm were subjected to slow freezing method using programmable freezer at 4°C for 3.5 hours and acrosome reaction treatment prior to Transmission Electron Microscopy (TEM) procedures. The results showed that the plasma and acrosomal membranes of the frozen-thawed sperm were expanded and the mitochondria became irregular in shape. On the otherhand, acrosome-reacted sperm showed ruptured plasma and acrosomal membrane and dispersion of the acrosome matrix. Frozen-thawed sperm also showed the dispersion of the acrosomal matrix within the plasma membrane. The nine outer-dense fibres of frozen-thawed and acrosome-reacted sperms were irregular in shape. No noticeable difference in the axoneme complex arrangement was observed in both samples. It can be concluded from our findings that the noticeable difference of the membranes and the mitochondria may cause the decrease in the sperm motility and subsequently a decrease in the rate of in vitro fertilization.